Pengaruh Strategi Operasional, Strategi Pemasaran, Dan Strategi Keuangan Terhadap Kinerja Perusahaan - Gunawan Aji; Intan Ayu Anggraini; Amirotul Mahfudhoh; Nadia Fitriatul Khasanah (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
This study aims to determine how the influence of operational strategy, marketing strategy, and financial strategy on better company performance. This research was conducted using a literature study, namely by looking for various references that have relevance to the research title. The research method used in this study is using a qualitative descriptive research method with the researcher as the object, where the researcher has the role of collecting, studying and describing all possibilities that will occur in the company. This research uses secondary data obtained from various kinds of literature studies using internet media in the form of online journals and books. The results of this study indicate that there is influence from the enactment of strategies carried out by companies such as operational strategies, marketing strategies, and financial strategies.